Outgroup homogeneity perception as a precursor to the generalization of threat across racial outgroup individuals: research report - Willscheid, Niclas; Bublatzky, Florian (Cortex, 2024)
People who look different from oneself are often categorized as homogeneous members of another racial group. We examined whether the relationship between such categorization and the tendency to generalize across outgroup individuals is explained by perceived visual similarity, leading to an all-look-alike misperception. To address this question at the neural level, White participants perceived sequences of White and Black faces while event-related electrocortical activity was recorded. Prior to each face sequence, one specific ingroup or outgroup face was instructed as a cue for receiving unpleasant electric shocks (threat cue), and we were interested in the extent to which such threat effects generalize to other non-instructed faces (safety cues). Face stimuli were presented in adaptor-target pairs, consisting of two ingroup faces or two outgroup faces, which could depict either the same or different identities. Results show less identity processing of outgroup compared to ingroup faces in early visual processing, i.e., N170 repetition suppression was sensitive only to ingroup face identities. Subsequently, as indicated by enhanced Late Positive Potentials to both threat and safety faces, instructed threat generalized stronger across outgroup compared to ingroup faces. These findings and their interaction suggest that the misperception of outgroup homogeneity may be an early precursor to the tendency to generalize threat associations across outgroup individuals.
Online verfügbar: 7. November 2024, Artikelversion: 20. November 2024
Gesehen am 29.04.2025